Radiofrequency tumor ablation system with a wireless or implantable probe. Issue 2 (12th September 2020) - Moore, Julian; Xu, Sheng; Wood, Bradford J.; Ren, Hongliang; Tse, Zion Tsz Ho
Abstract: Radiofrequency ablation (RFA) is a non-invasive image-guided procedure where tumors are heated in the body with electrical current. RFA procedures are commonly indicated for patients with limited local disease or who are not surgical candidates. Current methods of RFA use multiple cords and wires that ergonomically complicate the procedure and present the risk of cutting or shorting the circuit if they are damaged. A wireless RFA technique based on electromagnetic induction is presented in this paper. The transmitting and receiving coils were coupled to resonate at the same frequency to ensure the highest power output. The receiving coil was connected to two insulated electrodes on a catheter, which allowed the current to flow to the targeted tissue. The prototype system was tested with ex-vivo bovine tissue, which has similar thermal and electrical properties to human tissue. The setup can monitor the received power, efficiency, temperature, and ablation zone during ablation procedures. The maximum received power was 15 W, and the average maximum efficiency was 63.27%. The novel system was also able to ablate up to a 2 cm ablation zone in non-perfused tissue. This proof of concept for performing RFA wirelessly with electromagnetic induction may merit further optimization.